2005
DOI: 10.1088/1126-6708/2005/02/031
|View full text |Cite
|
Sign up to set email alerts
|

Non-supersymmetric black rings as thermally excited supertubes

Abstract: We construct a seven-parameter family of supergravity solutions that describe non-supersymmetric black rings and black tubes with three charges, three dipoles and two angular momenta. The black rings have regular horizons and non-zero temperature. They are naturally interpreted as the supergravity descriptions of thermally excited configurations of supertubes, specifically of supertubes with two charges and one dipole, and of supertubes with three charges and two dipoles. In order to fully describe thermal exc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(173 citation statements)
references
References 34 publications
5
168
0
Order By: Relevance
“…Recent work, e.g. [5][6][7][8][9], has shown that supergravity supertubes are part of a larger class of solutions of supergravity, called black supertubes, that saturate a Bogomol'nyi-Prasad-Sommerfeld (BPS) bound. These supersymmetric solutions in general possess three charges, three dipole moments, two independent angular momenta and an event horizon.…”
Section: Jhep03(2009)145mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work, e.g. [5][6][7][8][9], has shown that supergravity supertubes are part of a larger class of solutions of supergravity, called black supertubes, that saturate a Bogomol'nyi-Prasad-Sommerfeld (BPS) bound. These supersymmetric solutions in general possess three charges, three dipole moments, two independent angular momenta and an event horizon.…”
Section: Jhep03(2009)145mentioning
confidence: 99%
“…This family of solutions also contains BPS objects without event horizons, and the supertubes to which we refer in the present work belong to this family. Moreover, certain (non-supersymmetric) higher dimensional lifts of black rings, called black tubes, have been shown to correspond to excited states of two-charge and three-charge supertubes [5,9].…”
Section: Jhep03(2009)145mentioning
confidence: 99%
See 2 more Smart Citations
“…This fact leads to continuous non-uniqness. Following the same path that yields the three-charge rotating black holes [40]- [43], Elvang, Emparan and Figueras constructed a seven-parameter family of supergravity solutions that describe non-supersymmetric black rings and black tubes with three charges, three dipoles and two angular momenta [44].…”
Section: Introductionmentioning
confidence: 99%